3D printed concrete for large-scale buildings: An overview of rheology, printing parameters, chemical admixtures, reinforcements, and economic and environmental prospects. (November 2020) - Souza, Marcelo Tramontin; Ferreira, Igor Maia; Guzi de Moraes, Elisângela; Senff, Luciano; Novaes de Oliveira, Antonio Pedro
Abstract: This paper provides a comprehensive survey of current technological challenges and prospects for 3D printing technology with concrete applied to large-scale buildings. This innovative construction approach promises to revolutionize the shape of buildings with considerable time and cost savings but is still facing many technical and operational challenges. We gathered the knowledge of the most relevant and recent publications with our perception to address and discuss the main operational parameters, feasibility, and prospects for 3DPC technology. The paper is organized into five main categories: rheology of concrete for printing, effect of chemical admixtures, the role of reinforcements and inclusions, printing parameters and solutions for large-scale printers, and an analysis of economic and environmental aspects. Highlights: The printability is strictly related to the plastic viscosity and yield stress of concretes. The usage of chemical admixtures is essential to produce printable and buildable concretes. Eliminating manually-constructed formworks is the point to save costs and time. Projects must be reinvented to allows the usage of rebars. Controversial aspects related to economic and environmental sustainability are discussed.